Comparison of Live Rat Femoral Artery Model with Intraoperative Microvascular Anastomosis - Schaverien, Mark V.; Butler, Charles E.; Suami, Hiroo; Liu, Jun; Selber, Jesse C. (Journal of Reconstructive Microsurgery, 2017)
Background The live rat femoral artery model is the gold standard in high-fidelity simulation for microvascular anastomosis worldwide. Despite widespread use, there is a paucity of evidence for its validity. This study aims to determine the correlation between microvascular anastomosis in the live rat femoral artery model and clinical performance.Methods Twenty-nine microsurgical fellows were included in the study. At the beginning and end of the 1-year fellowship, fellows were assessed performing arterial microvascular anastomoses in the laboratory in a live rat femoral artery model. Each procedure was digitally video recorded and blinded. Fellows were also assessed in the operating room at the beginning and end of training performing microvascular anastomoses in multiple free flap cases. Validated tools were used for assessment, and duration of procedure was also recorded. The results from the evaluations were compared and interfellow comparisons were performed.Results At both the beginning and end of the fellowship, there was no significant correlation between clinical performance evaluations during operating room cases and laboratory evaluations. In the laboratory, higher performance scores were associated with faster times at both the beginning and end of the fellowship.Conclusion Contrary to conventional wisdom, microsurgical skill in the live rat femoral artery model in the laboratory does not correlate with clinical performance in the operating room. This calls into question the utility of this model for training purposes. Further research is necessary to corroborate these results and potentially establish experimental models with greater validity and reliability.
Keywords: rat model; intraoperative evaluation; comparison; fellow; microsurgery